A retrospective cohort study of patients diagnosed with bladder cancer referred with visible haematuria: the impact of source of referral on prognostic indicators. (November 2014) - Marzouk, Sherief; Lamb, Benjamin W; Harris, Andrew; Mecci, Ali Jibran; Gan, Jo Han; Allchorne, Paula; Green, James SA
Objective: Our aim was to establish whether there is a difference in prognostic indicators for bladder urothelial carcinoma (UC) between the patients referred via the 2-week wait (2WW) and those presenting to the emergency department (ED). Patients and methods: We performed a retrospective cohort study of all patients referred with visible haematuria, comparing tumour stage and grade between patients diagnosed with bladder UC via the ED and 2WW at two London hospitals. Results: From 09/2009−09/2011, 51 patients referred from the ED, and 146 from the 2WW clinic were diagnosed with bladder UC. Regarding tumour stage: 57% of the ED group had muscle-invasive UC compared with 23% from 2WW ( p =0.001). Regarding tumour grade: 82% of the ED group had G3 tumours, versus 54% from 2WW ( p <0.001). ED referrals were significantly older than those from the 2WW ( p <0.001). Conclusions: Patients with UC who present as emergencies had worse prognostic indicators and were older than those referred from the 2WW pathway. This supports the need for the inclusion of haematuria in the out-of-hours urology guidelines within the Acute Oncology Service.